Do you want to be my friend? - Carle, Eric. (New York : Philomel Books, 1988)
A mouse searches everywhere for a friend.
0.9
K-3
K-3
Keywords: Animals -- Juvenile fiction; Mice -- Juvenile fiction; Animals -- Fiction; Mice -- Fiction; Stories without words; Animals -- Fiction; Mice -- Fiction; Stories without words